Origin of High Mg and SO4 Fluids in Sediments of the Terceira Rift, Azores‐Indications for Caminite Dissolution in a Waning Hydrothermal System. (13th December 2019) - Schmidt, C.; Hensen, C.; Wallmann, K.; Liebetrau, V.; Tatzel, M.; Schurr, S. L.; Kutterolf, S.; Haffert, L.; Geilert, S.; Hübscher, C.; Lebas, E.; Heuser, A.; et al.
Abstract: During R/V Meteor cruise 141/1, pore fluids of near surface sediments were investigated to find indications for hydrothermal activity in the Terceira Rift (TR), a hyperslow spreading center in the Central North Atlantic Ocean. To date, submarine hydrothermal fluid venting in the TR has only been reported for the D. João de Castro seamount, which presently seems to be inactive. Pore fluids sampled close to a volcanic cone at 2, 800‐m water depth show an anomalous composition with Mg, SO4, and total alkalinity concentrations significantly higher than seawater and a nearby reference core. The most straightforward way of interpreting these deviations is the dissolution of the hydrothermally formed mineral caminite (MgSO4 0.25 Mg (OH)2 0.2H2 O). This interpretation is corroborated by a thorough investigation of fluid isotope systems (δ 26 Mg, δ 30 Si, δ 34 S, δ 44/42 Ca, and 87 Sr/ 86 Sr). Caminite is known from mineral assemblages with anhydrite and forms in hydrothermal recharge zones only under specific conditions such as high fluid temperatures and in altered oceanic crust, which are conditions generally met at the TR. We hypothesize that caminite was formed during hydrothermal activity and is now dissolving during the waning state of the hydrothermal system, so that caminite mineralization is shifted out of its stability zone. Ongoing fluid circulation through the basement is transporting the geochemical signal via slow advection toward the seafloor. Plain Language Summary: Hydrothermal vents are a common phenomenon in oceanic spreading centers worldwide. During Meteor cruise 141/1 we sampled sediments and extracted pore fluids to find the first indications for hydrothermal activity in the Terceira Rift. The results indicate that a hydrothermal vent close to a major volcanic cone formed in the past and seems to be in a waning state at present. Sampled fluids are enriched in total alkalinity, Mg and SO4 . We found that the most straightforward explanation for this unusual finding is the dissolution of the hydrothermally formed mineral caminite, a magnesium‐sulfate‐hydroxide‐hydrate. Caminite is a rare mineral but suggested to be abundant under specific conditions in hydrothermal recharge zones. We propose that caminite formed in the Terceira Rift is now dissolving as temperatures decline, and fluids enriched in Mg and SO4 are transported along deep‐rooted faults to the seafloor. Key Points: Anomalously high Mg and SO4 pore fluids in sediments of the Terceira Rift, Azores Indication for abundant caminite (Mg‐sulfate‐hydroxide‐hydrate) formation and dissolution in a hydrothermal recharge zone First indication for a deep submarine hydrothermal system in the slow‐spreading Terceira Rift